Implementation of Islamic Economic Systems in Poverty Reduction (Case Study in Sorong City, West Papua, Indonesia) - Muhammad Irfan Efendi; Elin Herlinawati (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
The evaluation of the poverty alleviation program in Sorong City has not been carried out optimally. This can be seen from the percentage of poor people since 2015 which has only decreased by 0,07% -1,93% per year even in 2016 it has increased by 0,29%. The implementation of the program has not been effective due to the lack of optimal management of funds as a special autonomous region and the limitations of social assistance funds in the Local Government Budget (APBD). Therefore, other sources of assistance are needed that can be used as a driver of poverty alleviation. One of them is through zakat, infaq, shodaqoh, and waqf (ZISWAF) which was adopted from the Islamic economic system. This study examines the application of Islamic economics in improving the welfare of the population in Sorong City, especially the poor. The research was conducted based on statistical data related to poverty and the Gini ratio from the Statistics Indonesia (BPS), APBD, and ZISWAF funds from the National Amil Zakat Agency (BAZNAS) in Sorong City. With the acceptance of ZISWAF, the high income of the community will be distributed to the low society so that it can improve welfare.